Bluetooth-based positioning techniques for the cold chain application. (5th July 2019) - Tsang, Y.P.; Choy, K.L.; Wu, C.H.; Lam, H.Y.; Ho, G.T.S.; Koo, P.S.
In cold chains, the essentials of cold storage are the chilling and freezing storage sections. Due to occupational safety concerns for the warehouse workers in such a cold environment, this paper describes a Bluetooth-based access management and positioning system (BAMPS) to monitor worker location and movement in chillers and freezers, inspired by the growth of internet of things. In complying with the ISO11079, their occupational safety in term of exposure duration and recovery time in cold environments can be controlled. The Bluetooth low energy module is used for the transmitting and receiving sensing data in the cold storage environment. The positioning module is designed using Kalman filtering to eliminate signal variations instead of pre-requested calibration. Hence, the workplace ergonomics and monitoring in cold storage environment are enhanced. The significance of BAMPS is in exploring occupational safety management and real-time positioning in cold storage facilities.